Development of Training Aids for Teaching-learning of Anatomy Incorporating the Views of Teachers and Students : A Prospective Study - Habib, Md Ahsan; Manara, Anju; Ayub, Mahmuda; Begum, Nasrin; Hossain, Sharmin; Hossain, Md Delowar (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Medical educationists in the field of anatomy are in search of alternative to the traditional anatomy education based on topographical structural anatomy. The integration of newer teaching modalities and modern technology is encouraging interest and enhancing retention of anatomical knowledge and its clinical relevance. Objective: This study was designed to build an instructional infrastructure keeping in mind the demand of students as well as teachers and to analyze the effect of developed models on the learning of anatomy of undergraduate students.Materials and Methods: This prospective descriptive study was carried out at the department of anatomy, Armed Forces Medical College (AFMC), Dhaka Cantonment in two stages, during the period of January 2016 to December 2016. In the first stage, infrastructural facilities were developed for intervention in target population. Anatomical models were prepared by copying selected real abdominal viscera and models. During the second stage, the term II students were exposed to the newly developed learning environment and they got assistance from teachers. At the end of the term, students’ views were taken using structured questionnaires. After the term examination opinion of the teachers were taken using separate structured questionnaires. Result of the term final was analyzed. Statistical analysis was made using Microsoft Excel and SPSS 19. Results: As per the opinion of the user around 3/4th perfection level was achieved in preparing model (students’ view 72.17±15.51% and teachers’ opinion 77.56±10.13%; p=0.31). Both students and teachers opined that they got good benefit (mean score 3.82± 0.64 and 4.11±0.33 respectively out of total score 1 to 5) from the use of models prepared at the department and issued to students. Of the studied students 96.9%, 87.5%, 87.5% and 90.6% expressed that figure/pictures, models, animations and movies and Power Point presentation respectively created positive interest among them and on their learning of anatomy. Only 7%, 6.1% and 2.6% students expressed that models, animations and movies and Power Point presentation respectively do not have positive role on their learning process. On the other hand 100% teachers opined that figure/pictures, models, animations and movies and Power Point presentation created positive interest in the students and on their learning of anatomy. Analysis of result of oral and practical part of top 80 students (65% of total) was done. Mean of percentage score of the students in term I and II examinations were 60.92±7.54 and 66.39±6.51 (p=00) and ranges 82.25 to 49.50 and 79.5 to 53.75 respectively. Conclusion: Both the teachers and students advised to make the training aids more available to the students by increasing the number and also emphasized on the improvement of quality. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 50-55